1994
DOI: 10.1095/biolreprod50.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Two Gonadotropin Receptors in the Salmon Gonad by in Vitro Ligand Autoradiography1

Abstract: Receptors for two salmon gonadotropins, GTH I and GTH II, were localized by use of in vitro ligand autoradiography of coho salmon gonads at various stages of sexual maturation. The results in both sexes revealed the presence of two types of GTH receptors: type I (GTH-RI), which interacts with both GTHs, and type II (GTH-RII), which interacts specifically with GTH II. GTH-RI was found at all stages of spermatogenesis examined and was localized on cells that were most likely Sertoli cells; however, it could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 51 publications
6
53
0
2
Order By: Relevance
“…This observation is in agreement with the expression of the gonadotropin receptor genes in the somatic testicular cells described previously in different teleostean fish species including zebrafish, catfish, eel, and coho salmon (Miwa et al 1994, Ohta et al 2007, Garcia-Lopez et al 2009. We further identified a number of genes upregulated in vitro by both Fsh and Lh that are also found to be naturally and strongly increased at the end of the reproductive cycle, when both gonadotropins and their receptors reach their maximum secretion and expression levels, respectively (Gomez et al 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is in agreement with the expression of the gonadotropin receptor genes in the somatic testicular cells described previously in different teleostean fish species including zebrafish, catfish, eel, and coho salmon (Miwa et al 1994, Ohta et al 2007, Garcia-Lopez et al 2009. We further identified a number of genes upregulated in vitro by both Fsh and Lh that are also found to be naturally and strongly increased at the end of the reproductive cycle, when both gonadotropins and their receptors reach their maximum secretion and expression levels, respectively (Gomez et al 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Among the genes preferentially regulated by Fsh, we found the transcripts that were previously shown to be expressed in the Sertoli cells, such as amh in fish (Skaar et al 2011) and Wisp1, Abca1, Smtn, Krt18, Slc40a1, Col1a1, Ccnd1, and Fstl3 in mice (Chalmel et al 2007). This is in agreement with the fact that the Fsh receptor would be the only gonadotropin receptor expressed in the salmonid Sertoli cells (Miwa et al 1994). The known or putative function of the Fsh-dependent genes will be detailed below.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to the high specificity of r-mtFSH and r-mtLH for their receptors, purified chum salmon FSH activated both types of GTH receptors with a slight preference for FSH-R, while LH did only LH-R (Oba et al 1999a,b). In in vitro ligand autoradiography, coho salmon FSH showed a specific interaction with FSH-R, whereas LH interacted with both FSH-R and LH-R (Miwa et al 1994), which is a similar situation in African catfish , channel catfish (Zmora et al 2003), and zebrafish ). Although we have no clear explanation for these different observations, these results may be attributed to high plasticity of gonadotropin-receptor interaction in teleosts and the use of heterologous GTHs from a different species.…”
Section: (B)mentioning
confidence: 62%
“…This is the first report on production of biologically active recombinant GTHs in salmonids, although pioneering researches on the fish GTHs and GTH receptors were carried out using salmon species (Suzuki et al 1988a,b, Yan et al 1992, Miwa et al 1994, Oba et al 1999a. In order to produce heterodimeric and biologically active recombinant GTHs, single-chain mtFSH and mtLH were constructed in which the carboxyl terminus of the mtFSHb or mtLHb subunit was fused to the amino terminus of the mature mtGTHa subunit with an intermediate polypeptide sequence (NCS).…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available on specific functions of FSH in spermatogenesis in fish; however, studies suggest that FSH stimulates spermatogonial proliferation in trout (Loir 1999) and 11-KT production in vitro (Planas & Swanson 1995). Furthermore, autoradiography studies in salmon localized FSH-R to presumed Sertoli cells, but could not determine whether Leydig cells contained FSH-R (Miwa et al 1994). More recently, Schulz et al (2003) reported that FSH also stimulates proliferation of Sertoli cells in African catfish.…”
Section: -Kt 1720 -P Fsh-r Lh-rmentioning
confidence: 99%